Assessing the Use of Econometric Analysis in Estimating the Costs of Meeting State Education Accountability Standards: Lessons from Texas - Imazeki, Jennifer; Reschovsky, Andrew (My University, 2005)
This assessment examines two methodologies to determine whether school districts have sufficient funds to meet accountability standards in Texas. One of the methodologies found the funds to be insufficient, while the other determined the support to be adequate. A lawsuit about the constitutionality of Texas school funding featured the two methodologies.